(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article examines contemporary educational and psychological methods for cultivating leadership attributes in female pupils. The text evaluates many leadership theories, encompassing personal, situational, motivational, and political aspects, and analyzes their application within educational contexts. The research underscores the significant influence of social and psychological elements on the development of leadership potential in female students, stressing the necessity of establishing supportive situations that cultivate leadership abilities. It examines the influence of gender views on leadership development, offering insights on how educational institutions might enhance support for female students in their leadership pursuits.